Differential gene expression along the animal-vegetal axis in the ascidian embryo is maintained by a dual functional protein Foxd - Tokuhiro, Shin-ichi (PLoS Genet, 2017)
In many animal embryos, a specific gene expression pattern is established along the animal-vegetal axis soon after zygotic transcription begins. In the embryo of the ascidian Ciona intestinalis, soon after the division that separates animal and vegetal hemispheres into distinct blastomeres, maternal Gata.a and β-catenin activate specific genes in the animal and vegetal blastomeres, respectively. On the basis of these initial distinct gene expression patterns, gene regulatory networks promote animal cells to become ectodermal tissues and vegetal cells to become endomesodermal tissues and a part of the nerve cord. In the vegetal hemisphere, β-catenin directly activates Foxd, an essential transcription factor gene for specifying endomesodermal fates. In the present study, we found that Foxd also represses the expression of genes that are activated specifically in the animal hemisphere, including Dmrt1, Prdm1-r.a (Bz1), Prdm1-r.b (Bz2), and Otx. A reporter assay showed that Dmrt1 expression was directly repressed by Foxd, and a chromatin immunoprecipitation assay showed that Foxd was bound to the upstream regions of Dmrt1, Prdm1-r.a, Prdm1-r.b, and Otx. Thus, Foxd has a dual function of activating specific gene expression in the vegetal hemisphere and of repressing the expression of genes that are normally expressed in the animal hemisphere. This dual function stabilizes the initial patterning along the animal-vegetal axis by β-catenin and Gata.a.